The Role of Islam Rahmat lil ‘Alamin as the Solution For Exclusive Life in Indonesia - Eka Apriani; Irwan Fathurrochman; Hendra Harmi (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Islam has given mercy to the development of languages, traditions, culture and arts found in various regions in Indonesia. Islam rahmatan lil alamin appears in the form of development and wealth of knowledge. However, Indonesia is not a religious country, but religious values are very dominant and very animating to the people in their personal lives, family, community, nation and state. Moreover, in the context of Indonesia, a country that is predominantly Muslim and becomes the foundation of the advancement of the Islamic world in the future, the spirit of religion cannot be separated from its people. In this case Islam appears as a religion that provides solutions in exclusive life, so as to create harmony that can lead to harmony in life. So the conclusion that we can take is that Islam as a religion that has the mission of rahmatanlil 'alamin must be the basis for every individual and group of Muslims to be tolerant and act well in spreading peace to all parties wherever and whenever Keyword: Islam, rahmatan lil alamin, exclusive life